Job Satisfaction as a Mediator of Work-Life Balance and Employee Performance: Evidence From The Regional Financial and Asset Management Agency - Sriutami, I Dewa Ayu Nyoman; Sili Antari, Ni Ni Luh; Karimi, Amir; Putu Santika, I (Journal of Management and Business Innovations, 2025)
This study stems from the growing awareness of the importance of maintaining a healthy balance between professional duties and personal life, particularly in enhancing job satisfaction and employee performance. The issue is especially pertinent at the Regional Financial and Asset Management Agency (BPKAD) of Badung Regency, where employees frequently face high workloads and tight deadlines. To examine this phenomenon, a quantitative research approach was adopted, employing the Partial Least Squares (PLS) method with SmartPLS 3 for data analysis. Out of a total population of 105 employees, 83 were randomly selected as respondents.The findings demonstrate that a well-maintained work-life balance significantly improves both job satisfaction and employee performance. Furthermore, job satisfaction emerges as a key determinant of productivity and serves as a mediating variable in the relationship between work-life balance and performance, strengthening the overall impact.Based on these insights, it is recommended that BPKAD Badung implement targeted strategies aimed at fostering a work culture that supports work-life balance and actively promotes employee satisfaction—two essential factors for enhancing individual performance and ensuring sustainable organizational growth. Keywords :  Employee Performance, Job Satisfaction, Work-Life Balance